STRATEGI REBRANDING WARTEG MENJADI MULTI OUTLET DAN MOBILE BISNIS (WARTEG KELILING) - Chrishardiyan, Febri; Pane, Monika Sarananta; Pambudi, Ghanindo Rachmat; Fachruroji, Addien; Santoso, Sugeng (Narada : Jurnal Desain dan Seni, 2022)
The transformation carried out in the warteg operating system (Warung Tegal) is one strategy in improving brand image and business mobility. The method used in this study is a case study using both a quantitative and qualitative approach. A data acquisition method using questionnaires and observations. The findings of this rebranding strategy have changed the brand image of warteg, which was originally a food that was easily displayed on traditional stalls, to stalls with better service standards, ordering options, general operation and quality. You can upgrade to. Permanent sales systems are also developed with mobile / mobile systems that use specially modified vehicles to move to crowded places and homes on a specific schedule and move beyond staying there. As the Warteg brand image grows, it is expected to help Warung tegal economists and users of the Waring brand increase sales in the competition in the culinary industry. The analytical tool used in this study was the logit model (Wald test), and the results of this study showed that the hypothetical results in the logit model reached 71.1% of the total.